Community Empowerment Model Through Village Cash For Work Program During The Covid-19 Pandemic - Siti Sumaryatiningsih; Hardjono Hardjono (Komunitas, 2023)
The Village Cash for Work Program meets the criteria for community empowerment. PKTD fulfills all aspects of community empowerment both definitively, principles, steps and goals according to Mardikanto's empowerment theory. The purpose of this study was to develop a model of community empowerment through PKTD during the pandemic in Bangunjiwo Village, Kapanewon Kasihan, Bantul Regency, DIY. This research is a qualitative research with a qualitative descriptive model. The analysis was carried out from the results of observations, interviews, documentation, written notes. In addition, as data triangulation, a Focus Group Discussion (FGD) was conducted which involved PKTD stakeholders. This research is located in Bangunjiwo Village, Kapanewon Kasihan, Bantul Regency, Special Region of Yogyakarta. The results of this study are that there are two models of community empowerment in Bangunjiwo. These two empowerment models are influenced by the geographical location of the program. The closer to the settlements has the higher the participation rate and the higher program outcomes. The changes of village fund priorities in 2020 with an allocation of 30% wages, and 2021 50% wages. Last, road class has an effect on the authority and subsequent compensation. So they need for a correct understanding of local village-scale assets and authorities.